Potassium deficiency aggravates yield loss in rice by restricting the translocation of non‐structural carbohydrates under Sarocladium oryzae infection condition. Issue 3 (4th March 2019) - Zhang, Jianglin; Lu, Zhifeng; Pan, Yonghui; Ren, Tao; Cong, Rihuan; Lu, Jianwei; Li, Xiaokun
Abstract : Sheath rot disease (ShR) caused by Sarocladium oryzae ( S. oryzae ) infection is an emerging disease that causes severe yield loss by restricting the translocation of non‐structural carbohydrates (NSC). Potassium (K) nutrition plays a critical role in disease resistance and the exportation of NSC. However, the physiological mechanisms of K with respect to ShR have not been thoroughly elucidated to date. The objectives of this study were to reveal the mechanisms by which K increases ShR resistance by regulating NSC translocation of rice, therefore, a field experiment combined with an inoculation experiment was conducted. We demonstrate that ShR disease incidence and disease index decreased dramatically with an increasing K application. K deficiency sharply induced the accumulation of NSC in the flag leaf (FL) and flag leaf sheath (FLS) under S. oryzae infection condition, which reduced the contribution of transferred NSC to final yield. A permutational multivariate analysis showed that K deficiency had a greater (49.0%, P < 0.001) effect on the NSC content variation in FL than that of S. oryzae infection (15.0%, P < 0.001). S. oryzae infection dramatically increased the difference in apparent transferred mass of NSC and cell membrane injury of diseased organs between K‐deficient and K‐sufficient rice. Finally, we demonstrate that cell membrane injury was a limiting factor imposed by K deficiency, which restricts the export of NSC from source organs. This work highlights the importance of K in improving ShR resistance by regulating NSC translocation (particularly the stem NSC).